2016
DOI: 10.1002/ijch.201600037
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to High‐resolution X‐ray Spectroscopic Measurements and their Applications in Bioinorganic Chemistry

Abstract: The bioinorganic chemistry community has had a long history of utilizing a diverse range of spectroscopic techniques to obtain detailed geometric and electronic structural insights into metalloprotein active sites. In recent years, the development of beamlines optimized for high‐resolution X‐ray spectroscopy has provided novel tools for the elucidation of biological active site structures. These methods include both non‐resonant and resonant X‐ray emission spectroscopy. Herein, we briefly introduce both X‐ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 96 publications
(156 reference statements)
1
56
0
Order By: Relevance
“…S3 and S5) that is in line with previous results. 30 We note that first moments have been shown to exhibit linear dependence on oxidation state, see for example 1s2p resonant inelastic X-ray scattering (RIXS) of Mn oxides, 39 Kβ 1,3 XES of Mn complexes, 16, 30, 33, 34 and Kβ 1,3 XES of PS II. 35 However, for PS II, RIXS experiments have demonstrated that the electron density is delocalized throughout the cluster compared to model complexes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S3 and S5) that is in line with previous results. 30 We note that first moments have been shown to exhibit linear dependence on oxidation state, see for example 1s2p resonant inelastic X-ray scattering (RIXS) of Mn oxides, 39 Kβ 1,3 XES of Mn complexes, 16, 30, 33, 34 and Kβ 1,3 XES of PS II. 35 However, for PS II, RIXS experiments have demonstrated that the electron density is delocalized throughout the cluster compared to model complexes.…”
Section: Resultsmentioning
confidence: 95%
“…13, 26 The set-up used a von Hamos spectrometer 9, 27 to measure the entire Kβ 1,3 emission spectrum on a shot-by-shot basis. 9, 16, 17, 27 The signal was collected on an ePix100 detector 28 with a pixel size of 50 μm. This leads to spreading of the charge cloud generated by a single X-ray photon over multiple pixels on the detector, also referred to as ‘charge-sharing’ for single photon events.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed explanations of the XAS and XES theories fall outside the scope of this paper and can be found in numerous recent reviews, on core‐level spectroscopy generality (de Groot and Kotani, 2008), XANES (Henderson et al, 2014; Joly and Grenier, 2016), EXAFS (Newville, 2014), XAS (Rehr and Albers, 2000; Ortega et al, 2012; Milne et al, 2014), XES (DeBeer and Bergmann, 2016), and HERFD (Bauer, 2014; Kowalska et al, 2016) applied to bioionorganic chemistry, and applications in environmental sciences (Gräfe et al, 2014). We will briefly recall the main principles of the core‐level spectroscopy techniques with special attention to effects that can be better analyzed with CAS.…”
Section: Methodsmentioning
confidence: 99%
“…Transition metals like Fe are known to exhibit a pre‐edge feature typically ∼10eV below the absorption edge. This appears more intense in noncentrosymmetric sites due to an electric dipole‐allowed transition between 1s and 4p and a dipole‐forbidden transition between 1s and 3d with quadrupole coupling . Hence, the pre‐edge feature involves contributions from both these dipole and quadrupole interactions.…”
Section: Introductionmentioning
confidence: 99%